Long-term recovery from substance use : European perspectives - Galvani, Sarah; Roy, Alastair; Clayson, amanda (Policy Press, 2022)
This cross-Europe analysis explores crucial aspects of long term recovery from substance use. Leading experts set out the evolving needs of people who have sought to change their use of substances and the factors in their progress. The book concludes with clear recommendations for improving future research, policy and practice.